Assignment under task dependent private information - Tan, Teck Yong (2022)
An agent's private information on his investment return is payoff-relevant only upon investment. This paper studies the contracting and assignment problem of a principal who can assign her agent to invest, which improves the agent's future productivity but allows the agent to exploit his private information for an information rent, or continuously produce, which prevents post-investment adverse selection but causes stagnation in productivity. With moral hazard in production, the optimal incentive contracts induce efficient production by agents without investment, but the improved productivity of any investment is under-exploited. A better distribution of investment returns can worsen inefficiency, with the principal possibly assigning less agents to invest.